Altered profile of circulating myokines as a predictor of poor prognosis in heart failure - Berezin, A. E.; Berezin, A. A.; Myrnyi, S. P.; Березін, Олександр Євгенійович; Мирний, Сергій Петрович (My University, 2020)
Background: The myokines are produced predominantly by skeletal muscle cells in response to physical activity and regulate metabolic homeostasis, proliferation, angiogenesis, neovascularization, reparation and neurogenesis in skeletal muscle tissue. HF is strongly associated with decrease in physical endurance and led to myopathy having established negative impact on the clinical outcomes and quality of life. The aim of the narrative mini review is depicted the role of the myokines in patients with heart failure (HF). Methods: Search in the data bases including SCOPUS, Web of Science, PubMed, Copernicus. Result: Impaired myokine (irisin, myostatin, myonectin, brain-derived neurotrophic factor, interleukins [IL]-6, IL-8, IL-15, tumor necrosis factor-alpha, fibroblast growth factor 21, growth differential factor-11) profile has been found in patients with HF regardless of phenotypes of cardiac dysfunction and, so important, prior to sarcopenia. It has been postulated that altered profile of the myokines can improve a stratification of HF patients at higher risk of poor clinical outcomes independently left ventricular ejection fraction and metabolic disease presentation. Conclusion: Myokines are involved in skeletal muscle myopathy and the evaluation of their circulating levels could provide new insights to the course of HF and stratify patients at higher risk of poor outcomes prior to sarcopenic stage. The large clinical trials are needed whether myokines are predictive biomarkers that are independently associated with an increased risk of HF-related mortality and clinical outcomes.
Keywords: Heart failure; Myokines; Outcomes; Sarcopenia; Risk stratification; Prognosis